Cardiac dysfunction induced by obesity es not related to beta-adrenergic system impairment at the receptor-signalling pathway - Ferron, Artur Junio Togneri; Jacobsen, Bruno Barcellos; Sant'Ana, Paula Grippa [UNESP]; Campos, Dijon Henrique Salomé de [UNESP]; Tomasi, Loreta Casquel de [UNESP]; Luvizotto, Renata de Azevedo Mello; Cicogna, Antonio Carlos [UNESP]; Leopoldo, André Soares; Lima-Leopoldo, Ana Paula (Public Library Science, 2015)
Obesity has been shown to impair myocardial performance. Some factors have been suggested as responsible for possible cardiac abnormalities in models of obesity, among them beta-adrenergic (βA) system, an important mechanism of regulation of myocardial contraction and relaxation. The objective of present study was to evaluate the involvement of βA system components in myocardial dysfunction induced by obesity. Thirty-day-old male Wistar rats were distributed in control (C, n = 25) and obese (Ob, n = 25) groups. The C group was fed a standard diet and Ob group was fed four unsaturated high-fat diets for 15 weeks. Cardiac function was evaluated by isolated papillary muscle preparation and βA system evaluated by using cumulative concentrations of isoproterenol and Western blot. After 15 weeks, the Ob rats developed higher adiposity index than C rats and several comorbidities; however, were not associated with changes in systolic blood pressure. Obesity caused structural changes and the myocardial responsiveness to post-rest contraction stimulus and increased extracellular calcium (Ca2+) was compromised. There were no changes in cardiac function between groups after βA stimulation. The obesity was not accompanied by changes in protein expression of G protein subunit alpha (Gsα) and βA receptors (β1AR and β2AR). In conclusion, the myocardial dysfunction caused by unsaturated high-fat diet-induced obesity, after 15 weeks, is not related to βAR system impairment at the receptor-signalling pathway.